Implementasi Program Jari Tangan: Analisis Pelaksanaan dan Dampaknya - Isyfi Syaufi Nafilah; Wazirul Luthfi; Winar Nur Aisyah Fatimah; Slamet Achrodi; Diaz Alvin Firdausa; Annisa Nur Fadhlillah (Jurnal Syntax Admiration, 2023)
The popularity of Corporate Social Responsibility (CSR) continues to rise, reflecting a company's commitment to addressing social and environmental issues to support sustainable development. As an example of CSR commitment, PT Pertamina EP Zona 7 Jatibarang Field has put this approach into practice. Their community development program, known as "Jari Tangan" (Independent Farming and Sustainable Food Production), is focused on developing sustainable horticulture cultivation. This research analyzes the implementation of the "Jari Tangan" program using a qualitative approach. The research findings demonstrate that this program has a positive impact on the local community in terms of economic, environmental, and social aspects. The program helps farmers increase their income, optimize land management, and introduce environmentally friendly farming practices. Additionally, the program introduces innovation in the form of the Bio-Cyclo Farming System, which helps address organic waste issues and enhances agricultural productivity. The success of the “Jari Tangan” program in Bongas Wetan Village extended to its replication in Karanganyar Village. This replication helped farmers enhance their rice harvests and income. The significance of the "Jari Tangan" program extends beyond the local context and aligns with broader sustainable development goals like poverty alleviation and sustainable agriculture improvement. The program's success is also recognized by the awards it has received in the field of CSR. Therefore, the "Jari Tangan" program not only serves as an example of a company actively engaged in sustainable development but also illustrates how appropriate innovations can generate significant positive impacts on society, the environment, and the economy.